2002
DOI: 10.1289/ehp.02110617
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of serum polychlorinated biphenyls and organochlorine pesticides measured in women from the child health and development study cohort, 1963-1967.

Abstract: We examined predictors of organochlorine concentrations in serum specimens from women who were pregnant in the 1960s and participated in the Child Health and Development Study in the San Francisco Bay Area of California. That study enrolled pregnant women at the Kaiser-Permanente Medical Facilities, conducted interviews, and drew blood specimens; these specimens were centrifuged and the resulting serum specimens were frozen and placed in long-term storage. For the current investigation, organochlorines were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 52 publications
10
85
2
Order By: Relevance
“…In our study, the median for these four congeners was 367 ng/g lipid and comparable to those of Faroe Islanders in 1994-1995 (median for the sum of 118, 138, 153 and 180 congeners ¼ 640 ng/g lipid) (Steuerwald et al, 2000). Other researchers have reported median PCB-153 values of: 30 (ng/g lipid) (Korrick et al, 2000) in US/ Massachusetts (1993-1998; 140 (ng/g lipid) (Walkowiak et al, 2001) in Germany/Dusseldorf (1993-1995; 100 (ng/g lipid) (Muckle et al, 2001) in Canada/Northern Quebec (1995)(1996)(1997)(1998); and 133 (ng/g lipid) (James et al, 2002) in US California (1964)(1965)(1966)(1967). In our study the median serum PCB-153 was 141 (ng/g lipid).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, the median for these four congeners was 367 ng/g lipid and comparable to those of Faroe Islanders in 1994-1995 (median for the sum of 118, 138, 153 and 180 congeners ¼ 640 ng/g lipid) (Steuerwald et al, 2000). Other researchers have reported median PCB-153 values of: 30 (ng/g lipid) (Korrick et al, 2000) in US/ Massachusetts (1993-1998; 140 (ng/g lipid) (Walkowiak et al, 2001) in Germany/Dusseldorf (1993-1995; 100 (ng/g lipid) (Muckle et al, 2001) in Canada/Northern Quebec (1995)(1996)(1997)(1998); and 133 (ng/g lipid) (James et al, 2002) in US California (1964)(1965)(1966)(1967). In our study the median serum PCB-153 was 141 (ng/g lipid).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the number of total months that a woman had breast-fed her children was also inversely associated with serum PCB levels, consistent with this route as an efficient means of excretion from the mother but a substantial source of exposure for the infant. Some studies have found an inverse association between pre-pregnancy BMI and serum PCB levels in pregnant women (James et al, 2002;Glynn et al, 2007). Glynn et al (2007) attribute this to a dilution effect associated with the rapid weight gain during pregnancy, which might be greater in those with high BMI to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…As the literature has shown (35,36), age and seafood intake are examples of exposure risk factors. N-3 fatty acids are known indicators of seafood intake (1), and we used the ratio of n-3/n-6 fatty acids as measures of seafood.…”
Section: Plasma Dioxin-like Activity In Greenlandic Inuit and Danish mentioning
confidence: 99%
“…In the body, organochlorine compounds reside mainly in adipose (80%), with rapid, passive distribution to blood and other tissues proportional to their neutral lipid content. Yet, body mass index (BMI; weight in kg divided by height in meters squared), a surrogate for adiposity, exhibits both positive and negative correlations with organochlorine compound levels in cross-sectional studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). On the other hand, reported relationships between BMI and elimination rate (expressed as rate constants or half-life) are consistently positive, such that a higher BMI results in a longer half-life (13,15,(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%